ANALISIS NERACA AIR LAHAN DI SUB DAS KRUENG JREUE KABUPATEN ACEH BESAR - MAWARDIANA MAWARDIANA; HELMI HASAN BASRI; TARMIZI TARMIZI (Jurnal Ilmiah Pertanian, 2018)
Krueng Aceh River Basin area (Krueng Jreue Sub-watershed) is a critical watershed, including a priority basin I of 23,218.06 ha. The research was conducted in Krueng Aceh River Basin (DAS), Krueng Jreue Sub-district of Aceh Besar. The study was conducted from December 2015 to February 2016. The research used Descriptive method with field survey and analysis in labotarium. This study aims to analyze the water balance of land in Krueng Jreue Sub-watershed. The methods used in the calculation of the water balance are Thornthwaite & Mather (1957). The results showed that the average water availability in Krueng Jreue Sub-watersheds on the highest land use varieties was found in November and the lowest in July. The rainfall surplus occurred from October to April (7 months) and the deficit occurred from May to September (5 months). In various types of land use, ground water averages are quite available from October to May (8 months), while less available in June until September (4 months). The highest percentage of groundwater was found in the primary forest (47.20%), while the lowest was in the bush (36.36%)